Correlated Cashflow Shocks, Asset Prices, and the Term Structure of Equity - Hasler, Michael; Khapko, Mariana (Management Science, 2023)
The term structure of equity risk premium is moderately downward-sloping unconditionally, markedly downward-sloping in good times, and markedly upward-sloping in bad times. An asset-pricing model featuring time-varying correlation between realized and expected cashflow shocks explains these puzzling empirical findings. Indeed, the model-implied slope of the equity term structure is in line with the data, both conditionally and unconditionally, because the estimated cashflow shock correlation is volatile, counter-cyclical, and negative on average. The model also generates realistic asset-pricing moments and a positive relation between the equity risk premium, slope of the equity term structure, and the dividend yield. This paper was accepted by David Sraer, finance. Funding: The authors thank the University of Texas at Dallas and the University of Toronto for financial support. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.4565 .